Aquaporin-Mediated Reduction in Maize Root Hydraulic Conductivity Impacts Cell Turgor and Leaf Elongation Even without Changing Transpiration - Ehlert, Christina (American Society of Plant Biologists, 2009)
Root hydraulic conductivity in plants (Lp(r)) exhibits large variations in response to abiotic stimuli. In this study, we investigated the impact of dynamic, aquaporin-mediated changes of Lp(r) on leaf growth, water potential, and water flux throughout the plant. For this, we manipulated Lp(r) by subjecting roots to four independent treatments, with aquaporin inhibitors applied either to transpiring maize (Zea mays) plants grown in hydroponics or to detopped root systems for estimation of Lp(r). The treatments were acid load at pH 6.0 and 5.0 and hydrogen peroxide and anoxia applied for 1 to 2 h and subsequently reversed. First, we established that acid load affected cell hydraulic conductivity in maize root cortex. Lp(r) was reduced by all treatments by 31% to 63%, with half-times of about 15 min, and partly recovered when treatments were reversed. Cell turgor measured in the elongating zone of leaves decreased synchronously with Lp(r), and leaf elongation rate closely followed these changes across all treatments in a dose-dependent manner. Leaf and xylem water potentials also followed changes in Lp(r). Stomatal conductance and rates of transpiration and water uptake were not affected by Lp(r) reduction under low evaporative demand. Increased evaporative demand, when combined with acid load at pH 6.0, induced stomatal closure and amplified all other responses without altering their synchrony. Root pressurization reversed the impact of acid load or anoxia on leaf elongation rate and water potential, further indicating that changes in turgor mediated the response of leaf growth to reductions in Lp(r).